ASP5878, a selective FGFR inhibitor, to treat FGFR3‐dependent urothelial cancer with or without chemoresistance. Issue 2 (February 2017) - Kikuchi, Aya; Suzuki, Tomoyuki; Nakazawa, Taisuke; Iizuka, Masateru; Nakayama, Ayako; Ozawa, Tohru; Kameda, Minoru; Shindoh, Nobuaki; Terasaka, Tadashi; Hirano, Masaaki; Kuromitsu, Sadao
Abstract : FGF/FGFR gene aberrations such as amplification, mutation and fusion are associated with many types of human cancers including urothelial cancer. FGFR kinase inhibitors are expected to be a targeted therapy for urothelial cancer harboring FGFR3 gene alternations. ASP5878, a selective inhibitor of FGFR1, 2, 3 and 4 under clinical investigation, selectively inhibited cell proliferation of urothelial cancer cell lines harboring FGFR3 point mutation or fusion (UM‐UC‐14, RT‐112, RT4 and SW 780) among 23 urothelial cancer cell lines. Furthermore, ASP5878 inhibited cell proliferation of adriamycin‐resistant UM‐UC‐14 cell line harboring MDR1 overexpression and gemcitabine‐resistant RT‐112 cell line. The protein expression of c‐MYC, an oncoprotein, in gemcitabine‐resistant RT‐112 cell line was higher than that in RT‐112 parental cell line and ASP5878 decreased the c‐MYC expression in both RT‐112 parental and gemcitabine‐resistant RT‐112 cell lines. Once‐daily oral administration of ASP5878 exerted potent antitumor activities in UM‐UC‐14, RT‐112 and gemcitabine‐resistant RT‐112 xenograft models without affecting body weight. These findings suggest that ASP5878 has the potential to be an oral targeted therapy against urothelial cancer harboring FGFR3 fusion or FGFR3 point mutation after the acquisition of gemcitabine‐ or adriamycin‐resistance. Abstract : ASP5878, a selective FGFR inhibitor, showed potent anti‐proliferative and antitumor activity in urothelial cancer cell line harboring FGFR3‐TACC3, FGFR3‐BAIAP2L1 or FGFR3 point mutation and their tumor xenografted models. ASP5878 also inhibited the proliferation of adriamycin‐resistant UM‐UC‐14 and gemcitabine‐resistant RT‐112 cell lines. These findings suggest that ASP5878, which is currently being evaluated in phase I clinical trials, has therapeutic potential against urothelial bladder cancers harboring FGFR3‐TACC3, FGFR3‐BAIAP2L1 or FGFR3 point mutation after the acquisition of gemcitabine‐ or adriamycin‐ resistance.